Prevalence of diphtheria in a tertiary care hospital of Western part of India – A clinicoepidemiological study - Mehta, Charul; Patel, Asmita; Singh, Diwakar; Patel, Bhavin (Indian Journal of Child Health, 2019)
Background: Diphtheria, a very common vaccine-preventable disease, is still persistent in India without much decline in the past decade. Objective: The objective of this study was to study the clinicoepidemiological profile of diphtheria in children up to 12 years of age, their outcome in tertiary care hospital of Western Gujarat. Materials and Methods: This prospective observational study was conducted among 164 children admitted in the tertiary hospital of Western Gujarat, who were diagnosed with during the period of July 2016–August 2018. Results: It was observed that the highest prevalence of diphtheria was seen in the age group of 5–9 years. There was slight male preponderance with 1.5:1. The majority of patients were referred from rural areas. Immunization status was the most determining feature as 68 patients out of the study population were unimmunized at the time of admission. Conclusion: The rise in the prevalence in more advanced age group of 8–12 years might be due to waning immunity and emphasizes on the need for increasing primary immunization coverage along with both booster doses in areas having less adequate health-care facilities or poor access.